Clinical NIRS of the urinary bladder – A demonstration case report. Issue 4 (2005) - Macnab Macnab, A. J. A. J.; Gagnon Gagnon, R. E. R. E.; Stothers Stothers, L. L.
Abstract : Urinary incontinence is a common affliction among people of all ages throughout the world. There are many causes of incontinence, treatment options are determined by the cause, and current diagnostic methods require urodynamic assessment, which involves urethral and rectal catheterization, which are uncomfortable and distasteful for patients. Since clinical near infrared spectrophotometry (NIRS) is a non-invasive, rapid means of measuring tissue oxygenation status at the bedside, we examined whether NIRS could be useful as a diagnostic tool for bladder dysfunction. An adult patient attending an incontinence clinic for routine urodynamic testing also had NIRS data collection during the standard bladder filling regimen. NIRS optodes were placed on the skin of the intact abdomen over the supra pubic region. Changes in oxy and de-oxy hemoglobin concentration and changes in cytochrome c oxidase net redox status via NIRS were collected at 6 Hz. The magnitudes of change that occurred during NIRS data collection are on the order of 0.5 µmol/l and the moments of change correspond to the subject's reported sensations of bladder filling and emptying, and with conventional urodynamics. These observations suggest that NIRS may be a disruptive technology with a role to play in non-invasive evaluation of bladder dysfunction in humans.